Model Pengembangan Wisata Bahari Wakatobi Berkelas Internasional. Studi kasus: Persepsi Penyelam Profesional - Michele Angelia; Kurniawan Gilang (Bisnis Event, 2023)
This research begin with careful observation when the researcher went to Wakatobi for scuba diving. Researcher finds Wakatobi is a beautiful destination both upper and under the sea. Researcher find that tourism development, infrastructure in Wakatobi did not suitable enough for their great potential to become big destination. Therefore, researcher search for suitable aspects to define Wakatobi as a prospect-full destination for diver. The research is about value chain analysis that includes all international class criteria for a destination. Purpose of this journal is to determine which is the most important points from diver’s perspective, based on their last experience in Wakatobi. The respondent is selected by asking whether they have been to Wakatobi for dive or not. The result of this research concludes that first priority to diver’s perspective is Food and Beverage, second is the tourism assets in destination, third accommodation. From nine aspects of value chain analysis about current condition, transportation got the lowest mean, and tourism assets got the highest mean. Therefore, the analysis of all points concludes into SWOT Analysis to determine strategies on how Wakatobi should be managed to become comprehensive and sustainable destination in the future.